The dark side of strengthening tax enforcement - Peng, Xinyi; Huang, Jian; Jin, Zhi; Chan, Kam C. (Technological and Economic Development of Economy, 2025)
Using the staggered adoption of China’s province-level Tax Administration Information System (TAIS) as an exogenous shock, we show that firms compromise employee workplace safety in response to strengthened tax enforcement driven by advances in tax collection technology. This effect is more pronounced in firms with significant prior tax avoidance, those under greater earnings pressure, and those where employees have limited bargaining power. Further analyses reveal that firms reduce employee workplace safety by cutting safety-related investments and increasing employee workloads. Collectively, our study highlights an unintended consequence of intensified tax enforcement on workplace safety.